Pengujian Biologis Formulasi Bioenkapsulasi Bacillus sp. untuk Menghambat Penyakit Layu Bakteri pada Tanaman Cabai - Saputra, Mochammad Mirza; Wuryandari, Yenny; Rahmadhini, Noni (Jurnal Agroekoteknologi, 2024)
Bacterial wilt disease is a serious threat to cayenne pepper plants because it can cause a significant reduction in production. Although Bacillus sp. has been applied using liquid formulations, the results have not been optimal. Therefore, bioencapsulated formulations in the form of Beads have been tested as an alternative to increase their effectiveness. These Beads were made using sodium alginate cross-linked with CaCl2 through an extrusion technique. The application of Beads with the K2W1 treatment combination showed the lowest disease intensity level, which was 55.5%, and the effectiveness of inhibition reached 44.5%. From the results of this study, it can be concluded that the beads formulation is significantly potentian in inhibiting bacterial wilt disease on chili plant